A vida dos presbíteros no Brasil sob a ótica dos ENPs. Desafios e perspectivas - Ferreira, Sandro (Revista Eclesiástica Brasileira, 2012)
O presente artigo enfoca a vida dos presbíteros no Brasil, apontando desafios e perspectivas, a partir dos ENPs (Encontros Nacionais de Presbíteros). Esses Encontros tiveram seu início no ano de 1985 e se constituíram como um momento forte de reflexão e debate sobre a vida e o ministério presbiteral, realizado a partir da perspectiva dos próprios presbíteros. Desde então, os ENPs somaram algumas conquistas, não obstante as resistências e os desafios. O presbítero, na Igreja e na sociedade, apresenta-se como alguém que cuida de diversas pessoas. Mas, enquanto cuidador, de que tipo de cuidados ele necessita? Quais são os desafios enfrentados pelos presbíteros brasileiros na ótica dos ENPs? Quais as contribuições desses Encontros Nacionais para os presbíteros do Brasil? Na tentativa de auxiliar os presbíteros a superarem os seus desafios pessoais e pastorais, os ENPs apontam para uma Pastoral Presbiteral que os ajude a enfrentar os obstáculos da vida comunitária, ou seja, unidos ao presbitério e em comunhão com o bispo, sem perder de vista que o presbítero evangeliza em conjunto com os leigos. Abstract: This research, aims to focus on the life of the priests of Brazil, pointing out some challenges and perspectives that derive from the CNM (Clergy National Meetings). The CNM begun to happen in 1985 and became an especial moment of reflection and debate on the priestly life and ministry from their own perspective. From its beginning until now, the CNM accumulated some victories, not without some kind of opposition and challenges. The priest emerges, within the church and the society, as someone who looks after many people. However, as people’s keeper, what kind of care he also needs? From the perspective of the CNM’s, what are the challenges faced by the Brazilian priests? What are the contributions of the National Meetings to the priests of Brazil? As an attempt to help priests to overcome their personal and pastoral challenges, the CNM look forward to a Pastoral care for the priests, which may help them to face the obstacles presented by the communitarian way of living, which means, to be united to the presbytery and in communion with the bishop, not forgetting that the presbytery evangelizes together with the lay people.